The Ides Of March : Representasi Etos Kerja Seorang Public Relation - Alfath Yosiana Putri (Jurnal Al-Hikmah: Jurnal Dakwah, 2019)
The film The Ides of March tells the work ethic of a public relations (PR). The purpose of this research is to find out the work ethic of PR practitioners in the film The Ides of March. This article is interpretive qualitative with the object of research is a PR on the film "The Ides of March”. Data is collected by viewing the film, then analyzing the conversation and visual of the film. The collected data were analyzed with Charles Sanders Peirce's semiotic theory techniques, including representamen, interpretants, and objects. The results of the analysis obtained 5 themes, namely Religion in politics, image formation, optimism, conflict management, and communication skills. The conclusion is that PR can win candidates who are supported due to political strategy and good PR communication skills. Keyword: The Ides of March film, work ethic, Public Relations Film The Ides of March menceritakan etos kerja seorang public relation (PR). Tujuan penelitian yaitu untuk mengetahui Etos Kerja Praktisi PR Dalam Film The Ides Of March. Artikel ini berjenis kualitatif interpretif dengan objek penelitian yaitu seorang PR pada film “The Ides Of March. Data dikumpulkan dengan melihat film, kemudian menganalisis percakapan dan visual film. Data yang terkumpul dianalisis dengan tehnik semiotika teori Charles Sanders Peirce, meliputi representamen, interpretant, dan object. Hasil analisis diperoleh 5 tema yaitu Agama dalam politik, pembentukan image, optimisme, managemen konflik, dan kemampuan komunikasi. Kesimpulannya yaitu PR dapat memenangkan calon yang didukung karena strategi politik dan kemampuan komunikasi PR yang baik. Kata Kunci: Film The Ides of March, etos kerja, Public Relation